2017
DOI: 10.1016/j.semcdb.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pore complex tethers to the cytoskeleton

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…Thus, the translocation of late endosomes into NEI and the biogenesis of nuclear membrane folds can be two linked events involving microtubules. In addition to the presence of microtubules in NEI, microtubules running parallel to the nuclear envelope and contacting the cytoplasmic filaments of a nuclear pore complex have been observed by electron microscopy [ 174 ]. Nucleoporin proteins are indeed present in NEI containing EV-loaded Rab7 + late endosomes [ 5 ].…”
Section: Nucleoplasmic Reticulum-associated Late Endosomes: a New mentioning
confidence: 99%
“…Thus, the translocation of late endosomes into NEI and the biogenesis of nuclear membrane folds can be two linked events involving microtubules. In addition to the presence of microtubules in NEI, microtubules running parallel to the nuclear envelope and contacting the cytoplasmic filaments of a nuclear pore complex have been observed by electron microscopy [ 174 ]. Nucleoporin proteins are indeed present in NEI containing EV-loaded Rab7 + late endosomes [ 5 ].…”
Section: Nucleoplasmic Reticulum-associated Late Endosomes: a New mentioning
confidence: 99%
“…Alternative tethering mechanisms include ZYG-12–microtubule binding, which is supported by the presence of microtubule binding domains in most mammalian hook proteins (Walenta et al. , 2001), and through nuclear pore–­microtubule binding, as identified in several metazoans (reviewed in Goldberg, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Centrosome-nuclear envelope tethering has also been suggested to occur through ZYG-12 dimerization between outer nuclear envelope and centrosome-based pools of the hook protein (Malone et al, 2003). Alternative tethering mechanisms include ZYG-12-microtubule binding, supported by the presence of microtubule binding domains in most mammalian hook proteins (Walenta et al, 2001), as well through nuclear pore-microtubule binding, as identified in several metazoans (reviewed in Goldberg, 2017).…”
Section: Discussionmentioning
confidence: 99%